Gene Therapy for Hepatocellular Carcinoma Using Adenoviral Vectors Delivering a Gene Encoding IL-17A-Neutralizing Antibody Fragments - Zou, Haoyu; Tuhin, Israth Jahan; Monty, Masuma Akter; Luo, Shenggen; Shao, Jiaqi; Yan, Zhiqiang; Yu, Lei (Human gene therapy, 2020)
High interleukin 17A (IL-17A) expression in hepatocellular carcinoma (HCC) tissue promotes HCC development. This study explores a method to inhibit HCC growth by neutralizing IL-17A in the HCC microenvironment. A novel type 5 adenoviral vector (Ad5) that carries DNA sequences encoding specific neutralizing IL-17A recombinant antibody fragments was developed in this research. After locally injecting into tumor tissues, the Ad5 transduced into tumor cells. This leads to the expression of the anti-IL-17A recombinant antibody fragments in the HCC tissue and consequently to an inhibition of HCC growth by neutralizing IL-17A. The stability of the antibody fragments was optimized by different structures design. Stable HCC cell lines that secrete IL-17A continuously were constructed, which showed stronger invasion and migration ability than control HCC cell lines. In addition, the enhanced migration and invasion ability were partially reversed by applying the adenoviral vectors. These results suggest that IL-17A might promote HCC growth by enhancing the invasion and migration ability of hepatoma cells. The antibody fragments from Ad5 neutralized IL-17A locally, in turn inhibiting the growth of HCC tumors. In conclusion, the local administration of Ad5 vectors encoding IL-17A-neutralizing antibody fragments provides a new option for HCC immunotherapy.